Oxygen-absorbent laminate for in-mold label
Patent Information
- Application Number
- JP2024165897
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-07-06
AI Technical Summary
Existing packaging technologies for foods, medical products, and chemical products suffer from insufficient oxygen barrier properties, leading to content deterioration, increased packaging costs, waste generation, and potential ingestion hazards, while existing oxygen-absorbing resins have issues with odor, solubility, and stability.
A laminate structure comprising a base material layer, oxygen barrier layer, oxygen-absorbing adhesive layer, and sealant layer, utilizing an oxygen-absorbing adhesive composition with unsaturated five-membered rings and an oxidation-promoting catalyst, which absorbs oxygen and reduces odor, enhancing barrier properties and sealability.
The laminate effectively reduces oxygen concentration, prevents content deterioration, and improves sealability, while minimizing odor and waste, offering a cost-effective and efficient packaging solution.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an oxygen-absorbing laminate for in-mold labels which generates little odor, has barrier properties against oxygen gas from the outside and absorbs oxygen within a content-storing space to suppress deterioration of the contents due to oxygen, and has an excellent balance between aroma retention, content resistance, and heat sealability, and is suitable for filling packaging; and to an oxygen-absorbing packaging material for in-mold labels, each made from the oxygen-absorbing laminate for in-mold labels, an oxygen-absorbing in-mold label, and an oxygen-absorbing in-mold label container made using the oxygen-absorbing in-mold label. [Background technology]
[0002] Conventional packaging methods for preventing the deterioration of the quality of contents, such as food, medical products, chemical products, and cosmetics, due to oxygen have included using packaging materials with high oxygen barrier properties, replacing the gas in the content storage area with an inert gas such as nitrogen gas, and including an oxygen scavenger packaged with reduced iron powder or the like. However, these have problems such as insufficient performance, increased packaging costs, increased waste, only functioning in moist environments, and the risk of accidental ingestion. Furthermore, Patent Document 1 describes a packaging material that uses a resin that has oxygen absorbing properties and emits little odor. However, this resin is polycyclododecene, which is insoluble in polar solvents and has no active hydrogen groups, and is therefore unsuitable as an adhesive raw material for packaging materials made of laminates. Furthermore, Patent Document 2 describes a laminating adhesive made of a resin using methyltetrahydrophthalic acid as a raw material having oxygen absorbing properties, but this adhesive has the drawback of being unstable due to its low oxygen absorbing properties. Patent Document 3 describes an oxygen-absorbing resin that is a thermoplastic resin having a repeating unit composed of a saturated five-membered ring having a substituent that contains a carbon-carbon double bond and a -CH=CH- group linking the saturated five-membered rings. However, this resin has drawbacks such as being difficult to use due to its poor solubility in solvents and emitting a strong odor. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 5873770 [Patent Document 2] Patent No. 5671816 [Patent Document 3] Patent No. 6505699 Summary of the Invention [Problem to be solved by the invention]
[0004] The object of the present invention is to provide an in-mold label laminate which generates little odor, has excellent barrier properties against oxygen gas, reduces the oxygen concentration by absorbing oxygen in a content storage space, thereby suppressing deterioration of the content due to oxygen, and has an excellent balance of heat sealability, low odor properties, low oxygen concentration, aroma retention, content resistance, and filling and packaging properties; and to provide an in-mold label packaging material, an in-mold label, and an in-mold label container produced using the in-mold label. [Means for solving the problem]
[0005] In order to solve the above problem, the inventors have discovered that a laminate including a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer formed from a specific oxygen-absorbing adhesive composition, and a sealant layer are laminated in this order, and further including a printed layer, can solve the above problem. That is, the present invention is characterized in the following points. 1. An oxygen-absorbing laminate for in-mold labeling, comprising a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order, and further comprising a printing layer, said oxygen-absorbing laminate being used for an in-mold label container, The oxygen-absorbing adhesive layer is a layer formed from an oxygen-absorbing adhesive composition, The oxygen-absorbing adhesive composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring; When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing laminate for in-mold labels. 2. The structure of the unsaturated five-membered ring, or the structure consisting of the unsaturated five-membered ring and organic group 1, is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. 2. The oxygen-absorbing laminate for in-mold label according to 1 above. 3. The organic group 2 includes a structural portion derived from an isocyanate compound, or an isocyanate compound and a hydroxyl group-containing compound. 3. The oxygen-absorbing laminate for in-mold label according to 1 or 2 above. 4. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof; 4. The oxygen-absorbing laminate for in-mold label according to 3 above. 5. The hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 5. The oxygen-absorbing laminate for in-mold label according to 3 or 4 above. 6. The organic group 2 does not have a crosslinkable functional group. 6. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 5 above. 7. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; 6. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 5 above. 8. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4): 6. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 5 above. [ka] [ka] [ka] [ka] (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3Each of the above is an organic group having one or more carbon atoms, contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 9. The oxygen-absorbing compound contains a compound represented by the following formula (5): 6. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 5 above. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. 10. The oxidation-promoting catalyst is a peroxide or a compound containing a cation consisting of a transition metal; 10. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 9 above. 11. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid. 11. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 10 above. 12. The oxygen absorbing adhesive composition further contains a modifier, The modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound. 12. The oxygen-absorbing laminate for in-mold label according to any one of 1 to 11 above. 13. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. 13. The oxygen-absorbing laminate for in-mold label according to 12 above. 14. The hydroxyl group-containing compound includes one or more selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof. 14. The oxygen-absorbing laminate for in-mold label according to 12 or 13 above. 15. An oxygen-absorbing packaging material for in-mold label, produced using the oxygen-absorbing laminate for in-mold label according to any one of 1 to 14 above. 16. An oxygen-absorbing in-mold label produced using the oxygen-absorbing packaging material for in-mold labels described in 15 above. 17. An oxygen-absorbing in-mold label container produced using the oxygen-absorbing in-mold label according to 16 above, The oxygen-absorbing in-mold label is in-molded onto the outer side surface of the body and / or the outer bottom surface of the bottom of the in-mold label container, The oxygen barrier layer is a layer located outside the oxygen absorbing adhesive layer. Oxygen absorbing in-mold label container. Effect of the Invention
[0006] According to the present invention, it is possible to obtain an in-mold label laminate which generates little odor, has excellent barrier properties against oxygen gas, absorbs oxygen in the content storage space to reduce the oxygen concentration and suppresses deterioration of the contents due to oxygen, and has an excellent balance of heat sealability, low odor, low oxygen concentration, aroma retention, content resistance, and filling and packaging properties, as well as an in-mold label packaging material, an in-mold label, and an in-mold label container produced using the in-mold label. Furthermore, packaging materials made from the laminate of the present invention are particularly suitable for flexible packaging applications, shortening the packaging process, reducing costs, and making the package lighter. Since the package does not require the inclusion of an oxygen absorber as was previously included, this eliminates the risk of the oxygen absorber being accidentally ingested and reduces the amount of waste consisting of the oxygen absorber. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the layer structure of an oxygen-absorbing laminate for in-mold label of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view showing an example of an oxygen-absorbing in-mold labeled container of the present invention. [Diagram 3] 1 is a perspective view showing an example of an oxygen-absorbing in-mold label of the present invention. [Figure 4] 1 is a perspective view showing an example of an oxygen-absorbing in-mold labeled container of the present invention. [Diagram 5] FIG. 2 is a cross-sectional view showing an example of a molding process for the oxygen-absorbing in-mold labeled container of the present invention. [Figure 6] FIG. 2 is a cross-sectional view showing an example of a molding process for the oxygen-absorbing in-mold labeled container of the present invention. [Figure 7] FIG. 2 is a cross-sectional view showing an example of a molding process for the oxygen-absorbing in-mold labeled container of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The present invention will be described in more detail below. The following description of the constituent elements is an example of an embodiment of the present invention, and the present invention is not limited to these contents as long as it does not exceed the gist of the present invention. In the present invention, the terms film and sheet have the same meaning.
[0009] <Oxygen-absorbing laminate for in-mold labels> The oxygen-absorbing laminate for in-mold labeling of the present invention is a laminate used for in-mold labels for in-mold labeled containers, and includes a layer structure in which at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer are laminated in this order, and further includes a printed layer. When forming an oxygen-absorbing in-mold labeled container (hereinafter sometimes referred to as an in-mold labeled container) using an oxygen-absorbing packaging material for an oxygen-absorbing in-mold label (hereinafter sometimes referred to as an oxygen-absorbing packaging material) made from the oxygen-absorbing laminate for in-mold labels (hereinafter sometimes referred to as an oxygen-absorbing laminate), the sealant layer is heat-sealed, and the oxygen barrier layer is located outside the in-mold labeled container relative to the oxygen-absorbing adhesive layer. By positioning the oxygen barrier layer outside the oxygen-absorbing adhesive layer, the amount of oxygen passing through the in-mold label container from the outside is reduced, and the efficiency with which the oxygen-absorbing adhesive layer absorbs oxygen in the content storage space and reduces the oxygen concentration is increased.
[0010] The oxygen-absorbing laminate for an in-mold label may contain layers having various other functions, if necessary. For example, it may have a base material layer or a printed layer, and may include a reinforcing layer to satisfy various conditions such as deformation resistance, drop impact resistance, pinhole resistance, heat resistance, sealability, quality maintenance, workability, hygiene, and the like. In addition, the packaging material may have a functional layer for improving the oxygen gas barrier property, imparting barrier properties against water vapor and the like, imparting aroma retention to the contents to be filled and packaged, and preventing the contents from having an unpleasant taste or odor. Furthermore, between or within each of the above layers, a general-purpose adhesive layer may be included to improve interlayer adhesion.
[0011] [Contents] In the above, examples of the contents include shampoo, detergent, chilled drinks, dairy products, ice cream, soup, prepared foods, and the like.
[0012] <Layers Constituting the Oxygen-Absorbing Laminate for In-Mold Labels> <Oxygen barrier layer> The oxygen barrier layer is a layer that, in an in-mold labeled container made from the oxygen-absorbing laminate for in-mold labeling, prevents oxygen from passing through the in-mold label from the outside of the in-mold labeled container to the internal content-accommodating portion. In an in-mold labeled container, the oxygen barrier layer is positioned outside the oxygen-absorbing adhesive layer, thereby suppressing the transmission of oxygen from outside the oxygen-absorbing in-mold labeled container, thereby enhancing the effect of the oxygen-absorbing adhesive layer absorbing oxygen in the content storage section of the oxygen-absorbing in-mold labeled container and reducing the oxygen concentration. The oxygen barrier layer can be made of various oxygen barrier materials. In addition, the oxygen barrier layer may be made of an oxygen barrier material that has gas barrier properties not only against oxygen but also against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc. In addition, a barrier material that has gas barrier properties against water vapor, light blocking properties against sunlight, aroma retention properties for the contents, etc. may be used in combination.
[0013] Specifically, the oxygen barrier material may be one or more selected from the group consisting of metal foil, resin film with an inorganic vapor deposition layer, and resin coating film or film made of an oxygen barrier resin. Examples of inorganic compounds in the inorganic vapor deposition layer include metals, metal oxides, metal nitrides, and metal carbides. Among the above, resin films with a metal vapor deposition layer, resin films with a metal oxide vapor deposition layer, and resin coating films or resin films made of barrier resins are particularly preferred, as they have excellent barrier properties against oxygen gas, water vapor, light blocking, aroma retention, etc., and are environmentally friendly in terms of disposal of the container.
[0014] A specific example of the metal foil is aluminum foil, the thickness of which is preferably 5 μm to 30 μm. Specific examples of metal elements constituting the above inorganic compounds include aluminum (Al), silicon (Si), magnesium (Mg), calcium (Ca), potassium (K), tin (Sn), sodium (Na), boron (B), titanium (Ti), lead (Pb), zirconium (Zr), yttrium (Y), zinc (Zn), vanadium (V), barium (Ba), and chromium (Cr).
[0015] Specific examples of inorganic compounds include metals, metal oxides, metal nitrides, and metal carbides made of the above-mentioned metal elements. In addition, indium tin oxide (ITO), SiO x C y Also included are composite inorganic compounds such as membranes. Specific examples of the inorganic compound of the inorganic vapor deposition layer include silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferable.
[0016] The average composition of an inorganic compound is expressed as, for example, SiO x , AlO x , SiO x C y MO x , M.O. x C y (In the formula, M represents a metal element, and the values of x and y depend on the metal element. The range of X is different for each.) In the case of metal oxides, the value of X can range from 0 to 2 for silicon, 0 to 1.5 for aluminum, 0 to 1 for magnesium, 0 to 1 for calcium, 0 to 0.5 for potassium, 0 to 2 for tin, 0 to 0.5 for sodium, 0 to 1.5 for boron, 0 to 2 for titanium, 0 to 1 for lead, 0 to 2 for zirconium, and 0 to 1.5 for yttrium. The above MO X In the case of x=0, it is metallic and not transparent, and in the range of x, The upper limit is the value when completely oxidized. In the present invention, silicon oxide and aluminum oxide are preferably used, and silicon oxide having an x value in the range of 1.0 to 2.0 and aluminum oxide having an x value in the range of 0.5 to 1.5 can be used. The oxygen barrier layer may be formed of one of these barrier materials, or may be a combination of two or more of them, or may be a mixture of two or more of them. It may be composed of one layer or multiple layers of the same or different compositions, and in the case of multiple layers, they do not have to be laminated adjacently.
[0017] As the resin film supporting the inorganic vapor deposition layer, a resin film that has excellent mechanical, physical, chemical and other properties, and is particularly strong and tough, and has heat resistance, can be used since the inorganic vapor deposition layer is provided on it.
[0018] Specifically, in the present invention, examples of the resin film supporting the inorganic deposition layer include polyester-based resin films such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), polyamide-based resin films such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin resins, polystyrene-based resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polybutene resin films, and other polyolefin films; Polyvinyl chloride resins, polycarbonate resins, polyimide resins, polyamideimide resins, polyarylphthalate resins, silicone resins, polysulfone resins, polyphenylene sulfide resins, polyethersulfone resins, polyurethane resins, cellulose resins, poly(meth)acrylic resins, polyvinylidene chloride films, acetal resin films, fluorine-based resins, and others can be used. In the present invention, it is preferable to use a resin film made of biaxially oriented polyethylene terephthalate, polyacrylonitrile, ethylene-vinyl alcohol copolymer, non-oriented polypropylene (CPP), low-density polyethylene, linear low-density polyethylene, or the like, which can be heat-sealed or bonded with an adhesive. The resin film used in the vapor-deposited resin film may be a resin film constituting a base layer.
[0019] As a method for forming an inorganic vapor deposition layer, the inorganic vapor deposition layer can be formed on a resin film using, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, an ion plating method, or a cluster ion beam method, or a chemical vapor deposition method (CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, or a photochemical vapor deposition method, using the inorganic compounds as raw materials.
[0020] More specifically, in the above-mentioned PVD method, for example, a take-up type deposition machine is used, and a resin film coming off a winding roll in a vacuum chamber is placed into a deposition chamber, where a deposition source heated in a crucible is evaporated, and if necessary, an inorganic deposition layer is formed on the resin film on a cooled coating drum through a mask while oxygen or the like is sprayed from an oxygen outlet, and then the resin film with the inorganic deposition layer formed thereon is wound up onto a take-up roll, thereby producing a resin film with an inorganic deposition layer according to the present invention.
[0021] Meanwhile, in the above-mentioned CVD method, a mixed gas of, for example, an organic silicon compound as a monomer gas, oxygen gas, an inert gas, etc., supplied from a vapor deposition raw material volatilization and supply device in the vapor deposition chamber, is introduced onto the surface of a resin film unwound from a winding roll arranged in a vapor deposition chamber, on the peripheral surface of a cooling electrode drum, and a resin film on which a vapor deposition layer of silicon oxide is formed by plasma can be produced.
[0022] In the above, the thickness of the inorganic vapor deposition layer is preferably 30 Å to 3000 Å, more preferably 40 Å to 2500 Å, and even more preferably 50 Å to 2000 Å, in order to obtain sufficient oxygen barrier properties. More specifically, in the above PVD method, the thickness of the inorganic vapor deposition layer made of aluminum oxide is preferably 30 Å to 1000 Å, and more preferably about 50 Å to 500 Å. In the above CVD method, the thickness of the inorganic vapor deposition layer made of silicon oxide is preferably 30 Å to 3000 Å, and more preferably 100 Å to 300 Å. In the above, in the case of an inorganic vapor deposition layer made of a metal oxide or an inorganic substance, if the thickness of the inorganic vapor deposition layer exceeds the above range, cracks or the like are likely to occur in the inorganic vapor deposition layer, and there is a risk that the barrier properties will be reduced due to warping, and there are problems such as high material costs, which are undesirable. Also, if the thickness is less than the above range, it is undesirable because it is likely to be difficult to achieve oxygen barrier properties.
[0023] An oxygen barrier resin coating film or an oxygen barrier resin film made of an oxygen barrier resin can also be used as an oxygen barrier material, and can simultaneously exhibit gas barrier properties against water vapor and the like, aroma retention, and the like. Examples of oxygen barrier resins include polyvinylidene chloride resins (PVDC), polyethylene It is possible to use films or coatings of resins with excellent gas barrier properties, such as steric resins, polyamide resins (particularly aromatic polyamides such as nylon MXD6), ethylene-vinyl alcohol copolymers (EVOH) with an ethylene content of 25 mol % to 50 mol % obtained by fully saponifying an ethylene-vinyl acetate copolymer (vinyl acetate is approximately 79 wt % to 92 wt %), polyvinyl alcohol, polyacrylonitrile, and others. The thickness of the oxygen barrier resin coating film or the oxygen barrier resin film is not limited, but is preferably 0.5 μm to 300 μm, and more preferably 1 μm to 100 μm. The resin film with an inorganic vapor deposition layer preferably has a water vapor permeability of 1.0 g / m2 or less, as measured in accordance with JIS K7129 under an environment of a temperature of 40° C. and a humidity of 100% RH. 2 d ay or less, more preferably 0.5 g / m 2 days or less, and more preferably 0.1g / m 2 If the water vapor transmission rate is within the above range, the product can be used outside the packaging. This can adequately prevent water vapor from entering the content-accommodating section inside the package from the outer periphery. The resin film with an inorganic vapor deposition layer preferably has an acid permeability of 1.0 cc / m2 or less as measured in accordance with JIS K7126 under an environment of 23° C. temperature and 90% RH. 2 At m·day or less, and more preferably 0.5cc / m 2 ·atm·day or less, More preferably, 0.1 cc / m 2 ·atm·day or less. Oxygen permeability is the above value. If this range is satisfied, it is possible to sufficiently prevent oxygen from entering the content-accommodating portion inside the package from the outside of the package.
[0024] When forming the inorganic deposition layer, SiO x Pretreatment such as plasma reduces the resin to be vapor-deposited. By cleaning the surface of the film and generating polar groups or free radicals on the surface, it is possible to increase the tight adhesion between the inorganic vapor deposition layer and the resin film. Furthermore, when two or more inorganic vapor deposition layers are continuously laminated using a plasma enhanced chemical vapor deposition apparatus consisting of at least two deposition chambers, each layer can be deposited so as to have high gas barrier properties, thereby achieving higher gas barrier properties than that of a single layer. Furthermore, by continuously depositing the layers without exposing them to the atmosphere, it is possible to prevent foreign matter, dust, etc., which may cause cracks, from being mixed between the inorganic vapor deposition layers, and the gas barrier properties are improved. Furthermore, if the compositions of the vapor-deposited layers are different, the inorganic vapor-deposited layers are different discontinuous layers, and therefore the permeation of oxygen gas, water vapor, and the like can be more efficiently suppressed.
[0025] When the oxygen barrier layer is formed of a resin film with an inorganic vapor deposition layer, the layer can be laminated by bonding the inorganic vapor deposition layer surface to the base layer via a general-purpose adhesive layer. When laminating a resin film with an inorganic vapor deposition layer, if necessary, in order to strengthen the adhesive strength with other layers, the surface of the resin film with an inorganic vapor deposition layer may be subjected in advance to a physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or a chemical surface treatment such as oxidation treatment using chemicals, to form a surface treatment layer.
[0026] <Oxygen-absorbing adhesive layer> The oxygen-absorbing adhesive layer is a layer formed using an oxygen-absorbing adhesive composition.
[0027] Oxygen-absorbing adhesive composition The oxygen-absorbing adhesive composition of the present invention is an oxygen-absorbing adhesive composition that contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst. The oxygen-absorbing adhesive composition may further contain a modifier, a diluting solvent, various additives, and the like, as necessary.
[0028] The oxygen-absorbing adhesive composition may be prepared by adding an oxygen-absorbing compound to an existing adhesive composition, or the oxygen-absorbing adhesive composition may be prepared using an oxygen-absorbing compound as a resin component. Here, the existing oxygen-absorbing adhesive composition may be a one-liquid oxygen-absorbing adhesive composition or a two-liquid oxygen-absorbing adhesive composition. The oxygen absorbing adhesive composition can contain one or more oxygen absorbing compounds. The oxygen-absorbing adhesive composition and / or the above-mentioned existing adhesive composition may be curable or non-curable. If it is curable, it may be any of thermosetting, photocurable, electron beam curable, etc. The oxygen absorbing compound may or may not react with components contained in existing adhesive compositions, or may react with other oxygen absorbing compounds. Depending on the presence or absence of the above reaction and the type of reaction, one or more oxygen absorbing compounds can be selected and used from among those having no functional group, those having a (co)polymerizable functional group, and those having a functional group capable of reacting as a base agent or a curing agent.
[0029] Specifically, for example, an oxygen absorbing compound without a functional group and / or an oxygen absorbing compound with a functional group can be added to a two-liquid urethane adhesive composition containing an isocyanate compound and a hydroxyl group-containing compound. In this case, the functional group is preferably an isocyanate group and / or a hydroxyl group. For example, the oxygen-absorbing adhesive composition can be prepared by combining the main component and curing agent with an isocyanate compound and an oxygen-absorbing compound having a hydroxyl group, with a hydroxyl group-containing compound and an oxygen-absorbing compound having an isocyanate group, or with an oxygen-absorbing compound having a hydroxyl group and an oxygen-absorbing compound having an isocyanate group. The oxygen absorbing adhesive composition is preferably a urethane-based oxygen absorbing adhesive composition.
[0030] The solid content in the oxygen-absorbing adhesive composition is not particularly limited, but is preferably 20% by mass or more and 100% by mass or less.
[0031] The content of the oxygen absorbing compound in the solid content excluding the oxidation-promoting catalyst in the oxygen absorbing adhesive composition is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, there is a risk that the oxygen absorption will be insufficient. When it is 100% by mass, it means that the oxygen absorbing compound can be used as a resin component of the adhesive composition, and it has sufficient adhesiveness by itself, has a functional group that can be cured by itself, or is used by mixing an oxygen absorbing compound having a functional group as a main agent and an oxygen absorbing compound having a functional group as a curing agent.
[0032] The content of the oxidation-promoting catalyst in the oxygen-absorbing adhesive composition is preferably 10 ppm or more and 6000 ppm or less relative to the oxygen-absorbing compound. If the content is less than the above range, the oxygen absorption may be insufficient, and if the content is more than the above range, the oxygen absorption is likely to become unstable, and the oxygen absorption may be consumed before the package is produced, which may impair the effect of inhibiting deterioration of the package contents due to oxygen after the package is produced.
[0033] [Oxygen absorbing compound] The oxygen absorbing compound of the present invention has oxygen absorbing properties, generates little odor, and can be used alone or as a mixture with a resin or a resin composition. The oxygen-absorbing compound of the present invention is an unsaturated five-membered ring-containing compound having one or more unsaturated five-membered rings, in which any bond between five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond, and a monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring. When there is one unsaturated five-membered ring, the five-membered ring or the organic group 1 has a functional group having active hydrogen, or a group in which the active hydrogen of the functional group having active hydrogen is substituted with a monovalent organic group 2, and when there are two or more unsaturated five-membered rings, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 that substitutes the active hydrogen of the active hydrogen group on each of the organic groups 1. When one molecule contains two or more such unsaturated five-membered rings, the unsaturated five-membered rings are bonded to each other via a structure in which an active hydrogen of a functional group having an active hydrogen on each of the five-membered rings or organic group 1 is substituted with a divalent or higher organic group 2. The unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule may each be one or two or more kinds, and the number may be one or two or more. The organic group 1 bonded to one unsaturated five-membered ring may be one or two or more. Furthermore, the oxygen-absorbing compound may be a mixture of molecules having two or more structures in which the types and numbers of the unsaturated five-membered ring, organic group 1, and organic group 2 present in one molecule are different, as described above.
[0034] Organic group 1 donates electrons to the unsaturated five-membered ring, thereby increasing the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring, thereby increasing the reactivity with oxygen and improving the oxygen absorbency. It is preferable that no electron-withdrawing group is bonded to the unsaturated five-membered ring, since the electron-withdrawing group is bonded to the unsaturated five-membered ring, the electron density of the carbon-carbon double bond portion of the unsaturated five-membered ring is lowered, the reactivity with oxygen is reduced, and the oxygen absorption is reduced. Specific molecular structures of the oxygen-absorbing compound include, for example, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1, one unsaturated five-membered ring bonded to a monovalent or divalent organic group 1 and a monovalent organic group 2 in that order, two unsaturated five-membered rings bonded via a divalent organic group 1 and a divalent organic group 2, and three unsaturated five-membered rings bonded via a divalent organic group 1 and a trivalent organic group 2.
[0035] In addition, the oxygen absorbing compound does not have to have a crosslinkable functional group, but can have one. The crosslinkable functional group may be a functional group that was possessed by the compound from which the organic group 2 is derived, or may be a functional group that has been added by chemical modification. Because the oxygen-absorbing compound has a crosslinkable functional group, when the oxygen-absorbing compound is mixed with a resin or a resin composition, the oxygen-absorbing compound has increased compatibility with the resin or the resin composition or becomes part of the crosslinked structure of the resin or the resin composition, making it less likely to bleed from the resin or the resin composition, or from the cured product of the resin composition, and the content of the oxygen-absorbing compound in the resin or the resin composition can be increased. Specific examples of the crosslinkable functional group include an aliphatic hydroxyl group, an aromatic hydroxyl group, an isocyanate group, an amino group, an epoxy group, a (meth)acrylic group, etc. Among these, an isocyanate group and an aliphatic hydroxyl group are preferred. When the oxygen-absorbing compound has a crosslinkable functional group, the number of the crosslinkable functional groups in one molecule is preferably 1 or 2 or more. In addition, the crosslinkable functional groups contained in one molecule may be one type or two or more types. The functional group equivalent of the crosslinkable functional group is not particularly limited, but is preferably 500 to 20,000, more preferably 1,000 to 15,000, and even more preferably 1,500 to 10,000.
[0036] The number average molecular weight of the oxygen absorbing compound is preferably 100 to 10,000, more preferably 200 to 5,000, and even more preferably 300 to 2,500. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.
[0037] The oxygen absorbing action of the oxygen absorbing compound of the present invention can be promoted by heating or adding a catalyst.
[0038] (unsaturated five-membered ring) The unsaturated five-membered ring of the oxygen-absorbing compound has a carbon-carbon double bond therein. Here, the carbon-carbon double bond is any bond between the five carbon atoms constituting the unsaturated five-membered ring, and there may be one or two carbon-carbon double bonds in one unsaturated five-membered ring. The carbon-carbon double bond reacts with oxygen molecules in the air and captures the oxygen molecules, thereby causing the oxygen absorbing compound to exhibit its oxygen absorbing properties. Examples of compounds from which the above-mentioned unsaturated five-membered ring or the unsaturated five-membered ring to which the electron-donating organic group 1 is bonded include cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof. The oxygen-absorbing compound can have an unsaturated five-membered ring derived from one or more of these selected from the group consisting of these. The concentration of the unsaturated five-membered ring in the oxygen-absorbing compound is not particularly limited, but is preferably 1% by mass or more and 70% by mass or less, and more preferably 5% by mass or more and 60% by mass or less. If the concentration is lower than the above range, the oxygen absorption is likely to be insufficient, and it is difficult to obtain an oxygen-absorbing compound with a higher absorption capacity than the above range, and the balance between various physical properties is likely to be poor.
[0039] (Electron-donating organic group 1) Specific examples of the organic group 1 include an alkyl group, an alkylene group, a cyclic alkylene group, etc. Among these, a cyclic alkylene group is preferable, and one which constitutes an aliphatic bicyclic alkylene group together with the unsaturated five-membered ring is more preferable. Specific examples of the cyclic alkylene group include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cycloheptylene group, a cyclooctylene group, etc. Among these, a cyclopentylene group is more preferable.
[0040] (Electron-withdrawing organic group) Specific examples of the electron-withdrawing group include a phenyl group, a phenylene group, a carbonyl group, and a halogen. Indenes and coumarones in which only these electron-withdrawing groups are bonded to an unsaturated five-membered ring have a low electron density in the carbon-carbon double bond portion of the unsaturated five-membered ring, which reduces the reactivity with oxygen and results in low oxygen absorption.
[0041] (Functional group having active hydrogen) A functional group having an active hydrogen is chemically reactive. Specific examples of the functional group having an active hydrogen include a primary amino group, a secondary amino group, an aliphatic hydroxyl group, an aromatic hydroxyl group, an imino group, a carboxyl group, a urethane group, and a urea group. Among these, a primary amino group, a secondary amino group, an aliphatic hydroxyl group, and an aromatic hydroxyl group are preferred, and an aliphatic hydroxyl group is more preferred.
[0042] (organic group 2) Organic group 2 is a monovalent and / or divalent or higher group that substitutes an active hydrogen of a functional group having an active hydrogen on the five-membered ring or organic group 1 and is bonded to the five-membered ring or organic group 1. When there are two or more such unsaturated five-membered rings in one molecule, the unsaturated five-membered rings are bonded to each other via a structure in which the active hydrogen of a functional group having an active hydrogen is substituted with a divalent or higher organic group 2. As a specific example, a functional group having an active hydrogen on organic group 1 reacts with an isocyanate group of an isocyanate compound having a structural portion from which organic group 2 is derived, and the active hydrogen is substituted for organic group 2, resulting in bonding via a urethane group. By bonding the organic group 2, the oxygen absorbing compound can have two or more of the unsaturated five-membered rings in one molecule, and further, can be mixed with a resin or a resin composition to prepare a mixture. In addition, the compatibility, dispersibility, and reactivity of the mixture and the cured product of the mixture can be adjusted to be soft.
[0043] The organic group 2 may be an aliphatic group, an aromatic group, or may have both an aliphatic group and an aromatic group. The organic group 2 present in one molecule of the oxygen-absorbing compound may be of one type or of two or more types. The organic group 2 is preferably a group containing a structural portion derived from an isocyanate compound and / or a hydroxyl group-containing compound. Here, the structural portion derived from an isocyanate compound and / or a hydroxyl group-containing compound includes a structural portion derived from a reaction product of an isocyanate compound and a hydroxyl group-containing compound.
[0044] (Isocyanate compounds) Examples of isocyanate compounds from which the organic group 2 is derived include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, diphenylether diisocyanate, hydrogenated diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret bodies, allophanate bodies, isocyanurate bodies (trimers), and various derivatives thereof. Among these, biuret bodies of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred. In the present invention, one or more types selected from the group consisting of these isocyanate-based compounds can be used as the origin of the structural portion of the monovalent and / or divalent or higher hydrocarbon group. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed.
[0045] The number average molecular weight of the isocyanate compound is preferably 100 to 10,000, more preferably 160 to 5,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.
[0046] (Hydroxy group-containing compound) The hydroxyl group-containing compound is a compound from which the above organic group 2 is derived, and has two or more hydroxyl groups. Examples of the hydroxyl group-containing compound include polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof. Among these, polyether polyols and polyolefin polyols are preferred. In order to prevent odor generation, the hydroxyl group-containing compound is preferably one that does not have a double bond in the aliphatic chain of the main skeleton or one that has two hydroxyl groups. Compounds that have a hydroxyl group at the end are preferred because they are more readily available, but they do not have to be at the end. In the present invention, one or more types selected from the group consisting of these can be used as the hydroxyl group-containing compound from which the organic group 2 is derived. When two or more types are used, two types may be used in the same molecule of the oxygen-absorbing compound, or molecules of the oxygen-absorbing compound having different types may be mixed. The number average molecular weight of the hydroxyl group-containing compound is preferably 500 to 10,000, more preferably 750 to 5,000, and even more preferably 1,000 to 3,000. If the number average molecular weight is smaller than the above range, it is likely to precipitate when mixed with a resin or a resin composition. If the number average molecular weight is larger than the above range, it is likely to require a large amount of dilution solvent to be contained when mixed with a resin or a resin composition because the viscosity of the mixture increases, making it difficult to obtain a thick film or layer, and coating suitability is likely to deteriorate.
[0047] Polyhydric alcohols Polyhydric alcohols are monomers having two or more hydroxyl groups. Specific examples of polyhydric alcohols include diols such as ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, cyclohexanedimethanol, 1,8-octanediol, 1,9-nonanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2,4-trimethyl-1,3-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,12-octadecanediol, and 2,2'-oxydiethanol, as well as glycerin, mannitol, and sorbitol. Among the above, ethylene glycol is preferred in terms of oxygen absorption.
[0048] Polyolefin polyol The polyolefin polyol is a polyolefin resin having two or more hydroxyl groups. Specific examples of polyolefin polyols include those whose main skeleton is a polyolefin such as polyethylene, polypropylene, polybutylene, polybutadiene, hydrogenated polybutadiene, polyisoprene, hydrogenated polyisoprene, ethylene-vinyl acetate copolymer, ethylene-ethyl (meth)acrylate copolymer, ethylene-(meth)acrylic acid copolymer, and ethylene-propylene copolymer, and which have a hydroxyl group. Among these, those having an ethylene-vinyl acetate copolymer or hydrogenated polyisoprene as the main skeleton are particularly preferred.
[0049] Polyether polyol Polyether polyol is a polyether resin having two or more hydroxyl groups. Polyether polyols are obtained, for example, by dehydration condensation of the above-mentioned polyhydric alcohols or polyolefin polyols, and have a polyether structure in the main skeleton and a hydroxyl group. Specific examples of polyether polyols include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene ether diol, polypropylene ether diol, polybutylene ether diol, glycerin-modified polyether polyols, etc. Among these, polypropylene ether diol is particularly preferred.
[0050] Polyester polyol The polyester polyol is a polyester resin having two or more hydroxyl groups. The polyester polyols are obtained, for example, by esterification reaction between various polyvalent carboxylic acids or derivatives thereof and the above-mentioned polyhydric alcohols, polyolefin polyols, polyether polyols, etc., and have a polyester structure in the main skeleton and hydroxyl groups. Specific examples of polycarboxylic acids include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, pimelic acid, azelaic acid, sebacic acid, suberic acid, glutaric acid, 1,4-cyclohexanedicarboxylic acid, and trimellitic acid. Derivatives of these polycarboxylic acids include esters, acid anhydrides, and acylation products. Among the above, in order to reduce crystallinity, two or more types of polyhydric alcohols and two or more types of Polyester polyols in combination with polyvalent carboxylic acids are preferred.
[0051] Polycarbonate polyol Polycarbonate polyol is a polycarbonate resin having two or more hydroxyl groups. Polycarbonate has a polyol-derived portion in the main skeleton, and this polyol-derived portion may be derived from the above-mentioned polyhydric alcohols, polyolefin polyol, polyether polyol, polyester polyol, or the like. Among these, polycarbonate polyols using two or more kinds of polyhydric alcohols in combination are preferred in order to reduce crystallinity.
[0052] Poly(meth)acrylic acid ester polyol The poly(meth)acrylate polyol is a (meth)acrylate (co)polymer having two or more hydroxyl groups. Poly(meth)acrylic acid ester polyol can be obtained, for example, by using a hydroxyl group-containing monomer such as 2-hydroxyethyl methacrylate or a (meth)acrylic acid ester having a hydroxyl group synthesized from one (meth)acrylic acid or a derivative thereof and one diol, and polymerizing the hydroxyl group-containing monomer with itself or copolymerizing it with a (meth)acrylic acid ester not having a hydroxyl group. As the diol used in synthesizing the (meth)acrylic ester having a hydroxyl group, the above-mentioned diols, polyolefin polyol, polyether polyol, etc. can be used. Among these, a poly(meth)acrylic acid ester copolymer using 2-hydroxyethyl methacrylate is preferred.
[0053] Phenoxy resin Phenoxy resin is a resin obtained by reacting a polyhydric phenol compound with a polyhydric epoxy compound, and has a structure in which an aliphatic hydroxyl group is generated at the bond formed by reaction between an aromatic hydroxyl group and an epoxy group. As the phenoxy resin, those obtained by reacting a bisphenol with a diglycidyl etherified bisphenol are readily available and are common. Examples of the polyhydric phenol compound include bisphenol A and bisphenol F, and examples of the polyfunctional epoxy compound include bisphenol A diglycidyl ether and bisphenol F diglycidyl ether. Among these, phenoxy resins using bisphenol A are preferred. The terminal of the phenoxy resin may be an aromatic hydroxyl group or an epoxy group.
[0054] · Urethane chain-extended polyol The urethane chain-extended polyol is a polyol having two or more hydroxyl groups, which is obtained by extending the above-mentioned hydroxyl group-containing compound with a urethane chain. The urethane chain-extended polyol can be obtained, for example, by polymerizing the above-mentioned various hydroxyl group-containing compounds with the above-mentioned isocyanate-based compounds to extend the urethane chain. If necessary, diamines or amino alcohols may be used in combination for polymerization. Among the above, urethane chain-extended polyols obtained by reacting the above-mentioned various hydroxyl group-containing compounds having hydroxyl groups at both ends with a diisocyanate compound are preferred.
[0055] (Specific examples of oxygen absorbing compounds) Specific examples of the oxygen-absorbing compound are given below. 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-indenol represented by formula (1), 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-indenamine represented by formula (1-b), and 3a,4,5 ,6,7,7a-Hexahydro-4,7-methano-1H-inden-1-ol is an example of an oxygen-absorbing compound that has one unsaturated five-membered ring and one organic group 1, and one organic group 1 has a hydroxyl group or an amino group as a functional group having active hydrogen. [ka] [ka] [ka]
[0056] The oxygen absorbing compound represented by formula (2) is, for example, a compound having a hydroxyl group, which is a functional group having an active hydrogen on organic group 1 of the oxygen absorbing compound represented by formula (1), and an isocyanate compound R 1 (NCO) a The isocyanate group of the hydroxyl group reacts with the The active hydrogen is replaced, and a number of the unsaturated five-membered rings and the organic group 1 are R 1 It can be obtained by combining through It is an oxygen absorbing compound that can [ka] (In the formula, a is a number of 1 or more, and R 1 is an organic group having one or more carbon atoms, and It may contain an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0057] The oxygen absorbing compound represented by formula (5) is a compound represented by formula (2) in which a=2 and R 1 For example, the isocyanate compound OCN-R 4 -NCO and hydroxyl group-containing compound HO-R 5 Oxygen absorption when the group is derived from -OH and contains a structural part generated by the reaction of the two It is a volatile compound. [ka] (In the formula, f is a number equal to or greater than 0, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and further may contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0058] The oxygen-absorbing compound represented by formula (3) may be, for example, 1Isocyanate The oxygen-absorbing compound is derived from a nate compound and a hydroxyl group-containing compound, contains a structural portion formed by the reaction of the two, and contains hydroxyl groups as a result of residual excess hydroxyl groups or chemical modification. [ka] (In the formula, b and c are each a number equal to or greater than 1; R 2 is an organic group having one or more carbon atoms, The polyol may contain at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0059] The oxygen-absorbing compound represented by formula (4) may be, for example, 1 Isocyanate The oxygen-absorbing compound is derived from a hydroxyl group-containing compound and a carboxylate-based compound, contains a structural part formed by the reaction of the two, and contains an isocyanate group due to residual excess isocyanate groups or chemical modification. [ka] (wherein, d and e are each a number equal to or greater than 1; R 3 is an organic group having one or more carbon atoms, The polyol may contain at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
[0060] [Oxidation promotion catalyst] The oxidation-promoting catalyst is a compound that promotes the action of the oxygen-absorbing compound absorbing oxygen molecules and being oxidized. Examples of the oxidation-promoting catalyst include peroxides and compounds containing cations made of transition metals. Specific examples of the peroxide include hydrogen peroxide. The compound containing a cation made of a transition metal is preferably a metal soap made of a transition metal-containing compound capable of releasing a cation or complex of a transition metal atom and an anion or ligand made of a fatty acid. As the transition metal, cobalt, manganese, iron, nickel, copper, etc. are preferred, and as the anion or ligand, anion or ligand formed of stearic acid, naphthenic acid, octylic acid, acetylacetonate, etc. are preferred. The oxidation-promoting catalyst may be a metal soap formed by combining a cation made of one or more transition metals selected from the group consisting of the above transition metals with an anion made of one or more fatty acids selected from the group consisting of the above long-chain fatty acids. Specific compounds include cobalt octylate, cobalt acetylacetone (II), cobalt acetylacetone (III), manganese acetylacetone (III), and iron acetylacetone (III).
[0061] [Denaturant] The modifier is a compound having a functional group that reacts with the oxygen absorbing compound when the oxygen absorbing compound has a functional group, and various reactive monomers and resins can be used. By including a modifier in the oxygen-absorbing adhesive composition, it is possible to bond the oxygen-absorbing compound to other components in the oxygen-absorbing adhesive composition, to adjust the content of the oxygen-absorbing compound in the oxygen-absorbing adhesive composition, and to adjust the hardness of the cured product of the oxygen-absorbing adhesive composition.
[0062] For example, when the oxygen absorbing compound has a hydroxyl group or an isocyanate group, a modifying agent made of an isocyanate compound and / or a hydroxyl group-containing compound can be used. When the oxygen-absorbing adhesive composition is a urethane-based one, the equivalent ratio NCO / OH of the oxygen-absorbing adhesive composition is preferably 0.5 or more and 8 or less. If it is less than the above range, the curing of the oxygen-absorbing adhesive composition may be insufficient, and sufficient lamination strength (adhesive strength) may not be obtained, whereas if it is greater than the above range, the pot life of the oxygen-absorbing adhesive composition may be too short.
[0063] (Isocyanate compounds for use as modifiers) The isocyanate compound for the modifier can be the isocyanate compound used in the synthesis of the oxygen absorbing compound, and any of aromatic isocyanates, aliphatic isocyanates, and urethane chain-extended isocyanates thereof can be used. In addition, in order for the oxygen absorbing adhesive composition to harden, it is preferable to use one having two or more isocyanate groups in one molecule. However, it is also possible to use an isocyanate compound having one isocyanate group in one molecule in the range that does not inhibit the sufficient effect of the oxygen absorbing adhesive composition. As the isocyanate compound having two or more isocyanate groups in one molecule, a biuret form of hexamethylene diisocyanate is particularly preferred.
[0064] Specific examples of the isocyanate compounds include tetramethylene diisocyanate, hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, norbornane diisocyanate, xylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, phenylene diisocyanate, Examples of the isocyanate include toluene diisocyanate, diphenyl ether diisocyanate, polymethylene polyphenyl polyisocyanate, and their trimethylolpropane adducts, biuret forms, allophanate forms, isocyanurate forms (trimers), and various derivatives thereof. Among these, biuret forms of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate are preferred.
[0065] (Hydroxyl-containing compounds for use as modifiers) The hydroxyl group-containing compound for the modifier can be the hydroxyl group-containing compound used in the synthesis of the oxygen absorbing compound, and can be any of aromatic hydroxyl group-containing compounds, aliphatic hydroxyl group-containing compounds, and urethane chain-extended polyols thereof. In addition, in order for the oxygen absorbing adhesive composition to harden, it is preferable to have two or more hydroxyl groups in one molecule. However, a hydroxyl group-containing compound having one hydroxyl group in one molecule can also be used in combination within a range that does not inhibit the sufficient effect of the oxygen absorbing adhesive composition. As the hydroxyl group-containing compound having two or more hydroxyl groups in one molecule, either an aromatic hydroxyl group-containing compound or an aliphatic hydroxyl group-containing compound can be used, and either an alcohol-based or a phenol-based compound can be used. As the isocyanate compound having two or more isocyanate groups in one molecule, polyalkylene ether diols and urethane chain extended polyols of polyalkylene ether diols are particularly preferred.
[0066] [Dilution solvent] The dilution solvent is not particularly limited as long as it uniformly dissolves or disperses the oxygen-absorbing compound and the oxidation-promoting catalyst, makes the oxygen-absorbing adhesive composition uniform, and is compatible with the dry lamination process. For example, an ester-based dilution solvent, a ketone-based dilution solvent, a hydrocarbon-based dilution solvent, etc. can be used. Specific examples of the ester-based diluent solvent include ethyl acetate, butyl acetate, etc., specific examples of the ketone-based diluent solvent include methyl ethyl ketone, etc., and specific examples of the hydrocarbon-based diluent solvent include toluene, etc. Among these, ethyl acetate is easy to use and is preferable.
[0067] [Various additives] The oxygen-absorbing adhesive composition may contain various additives as necessary. For example, curing accelerators, curing regulators for extending the pot life, antioxidants for suppressing a decrease in oxygen absorption during storage or use of the oxygen-absorbing adhesive composition and before the contents are placed in a package, adhesion aids, tackifiers, leveling agents, ultraviolet absorbers, defoamers, coloring pigments, and extender pigments may also be added.
[0068] (Cure accelerator) There are no particular limitations on the curing accelerator that can be used as long as it accelerates the curing reaction of the oxygen-absorbing adhesive composition. Specific examples of the curing accelerator include metal-containing compounds such as dibutyltin dilaurate, dibutyltin diacetate, dioctyltin dilaurate, dibutyltin dimaleate, tetrabutyl titanate, and tetraisopropyl titanate, and tertiary amines such as 1,8-diaza-bicyclo(5,4,0)undecene-7, 1,5-diazabicyclo(4,3,0)nonene-5, and triethanolamine. One or more types selected from the group consisting of these can be used.
[0069] (hardening regulator) When the pot life of the oxygen-absorbing adhesive composition is shortened due to the oxidation-promoting catalyst contained therein, the pot life can be extended by using a cure regulator in combination. Specific examples of the hardening regulator include phosphoric acids, such as orthophosphoric acid, metaphosphoric acid, polyphosphoric acid, and ester derivatives thereof. One or more selected from the group consisting of these can be used. The amount of reaction regulator added is preferably 200 ppm or more and 400 ppm or less based on the resin component of the oxygen-absorbing adhesive composition. If the amount is less than this range, it is difficult to obtain the effect of extending the pot life, and if the amount is more than this range, there is a risk that the curing of the oxygen-absorbing adhesive composition is inhibited.
[0070] (Antioxidants) The oxygen-absorbing adhesive composition may contain an antioxidant in order to suppress deterioration of oxygen absorption properties during storage or use of the oxygen-absorbing adhesive composition, and even in processes before a package made using the oxygen-absorbing adhesive composition contains contents, and to maintain high oxygen absorption properties after the contents are contained. Specific examples of the antioxidant include phenols, lactones, thioethers, gallic acids, ascorbic acid, erythorbic acid, catechin, dibutylhydroxytoluene, tocopherol, citric acid, butylhydroxyanisole, phosphite, hindered amines, and aromatic amines. One or more selected from the group consisting of these antioxidants can be used. In addition, when it is assumed that heat or light is used as a trigger for expressing oxygen absorbing ability, it is preferable to use an antioxidant having low heat resistance and light resistance, such as ascorbic acid or tocopherol, and it is not preferable to use an antioxidant having high heat resistance and light resistance, such as a phenol-based antioxidant. The amount of the antioxidant added is preferably 10 ppm or more and 10000 ppm or less relative to the oxygen absorbing compound. If the amount is less than the above range, the antioxidant effect is likely to be insufficient, and if the amount is more than the above range, there is a risk that the oxygen absorbing ability will decrease.
[0071] (Adhesive assistant) As an adhesion aid for aiding adhesive strength, a silane coupling agent is preferred. Examples of the silane coupling agent include γ-glycidoxypropyltrialkoxysilane, γ-methacryloxypropyltrialkoxysilane, γ-glycidoxypropylmethyldialkoxysilane, β-(3,4-epoxycyclohexyl)ethyltrialkoxysilane, γ-aminopropyltrialkoxysilane, γ-aminopropylmethyldialkoxysilane, N-(β-aminoethyl)-γ-aminopropyltrialkoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldialkoxysilane, N-butyl-3-amino-2-methylpropyltrialkoxysilane, γ-mercaptopropyltrialkoxysilane, and γ-mercaptopropylmethyldialkoxysilane. The alkoxy group is preferably a methoxy group or an ethoxy group, and one or more selected from the group consisting of these can be used.
[0072] (tackifier) Examples of the tackifier include paraffin wax, polyethylene wax, rosin, rosin glycerin ester, terpene, and alkylphenol. One or more types selected from the group consisting of these can be used.
[0073] (Leveling agent) The leveling agent may be an acrylic polymer-based agent, a modified silicone-based agent, an acetylene diol-based agent, or the like. One or more types selected from the group consisting of these may be used.
[0074] (UV absorber) UV absorbers include benzotriazoles, hydroxyphenyltriazines, One or more types selected from the group consisting of these may be used.
[0075] (Antifoaming agent) The antifoaming agent may be a surfactant, polyether-modified silicone oil, or the like, and one or more selected from the group consisting of these may be used.
[0076] (Color pigments) Examples of color pigments include organic pigments such as anthraquinone, diketopyrrolopyrrole, perylene maroon, carbon black, dioxazine, perylene, benzimidazolone, isoindolinone, isoindoline, phthalocyanine, and indanthrene, and inorganic pigments such as yellow iron oxide, red iron oxide, azomethine copper complex, titanium oxide, and silicon oxide. One or more types selected from the group consisting of these can be used.
[0077] (Extender pigment) The extender pigment is a white or colorless pigment that is used as an extender or as an adjuster for coloring power, gloss, strength, usability, etc. Specific examples include inorganic pigments such as barium sulfate, barium carbonate, calcium carbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, barium titanate, calcium hydroxide, calcium sulfite, calcium sulfate, calcium oxide, calcium silicate, titanium oxide, silica, zeolite, and talc, and one or more types selected from the group consisting of these can be used.
[0078] <<Method for preparing oxygen-absorbing adhesive composition>> The oxygen-absorbing adhesive composition can be produced by mixing all of the components, such as the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the diluting solvent, the various additives, etc. Alternatively, the oxygen-absorbing adhesive composition can be produced by mixing the oxygen-absorbing compound, the oxidation-promoting catalyst, and, if necessary, the modifier, the diluting solvent, the various additives, etc., with an existing adhesive composition. The method for carrying out the above mixing and the order in which the components are mixed are not particularly limited, and the method and mixing order used in preparing a general adhesive composition can be applied. Specific mixing methods include a method of dissolving in a solvent and mixing, and a method of melt-kneading. In this case, it is preferable to adjust the heating temperature in order to increase the solubility or dispersibility.
[0079] <<Method of using the oxygen-absorbing adhesive composition>> There are no particular limitations on the method of using the oxygen-absorbing adhesive composition, and any method for using it as an adhesive can be used. For example, there may be mentioned a non-solvent type lamination method in which the coating is heated to obtain an appropriate viscosity, and a dry lamination method in which a dilution solvent or other compounded adhesive is added to adjust the coating viscosity to an appropriate level. When forming an adhesive layer using the oxygen absorbing adhesive composition, the coating amount is 2 to 5 g / m 2 is preferable, and 3 to 5 g / m 2 If the amount is less than the above range, sufficient oxygen absorbency may not be obtained, whereas if the amount is more than the above range, the oxygen absorbency does not change significantly, leading to a cost disadvantage, which is undesirable.
[0080] A laminate obtained by forming and bonding an adhesive layer using the oxygen-absorbing adhesive composition is preferably aged at 20° C. or higher and 50° C. or lower for 2 days or higher and 5 days or lower. In addition, in order not to decrease the oxygen absorption property of the laminate, it is preferable to carry out the aging at a temperature as low as possible or in an inert gas atmosphere. When storing the produced laminate, it is preferable to store it at 10° C. or below or in an inert gas atmosphere in order not to decrease the oxygen absorbing property of the laminate.
[0081] About objects that can be glued There are no particular limitations on the objects to which the oxygen-absorbing adhesive composition can be adhered, and the composition can be adhered to, for example, resin molded products, resin films, paper, metals, metal foils, inorganic vapor-deposited film surfaces, and inorganic oxide vapor-deposited film surfaces.
[0082] Specific examples of resins for the resin film include polyester-based resins such as polyethylene terephthalate (PET), polyamide-based resins such as various nylons, polyethylene-based resins, polypropylene-based resins, cyclic polyolefin-based resins, polystyrene-based resins, polyolefin-based resins such as acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), and polybutene-based resins, polyvinyl chloride-based resins, polycarbonate-based resins, polyimide-based resins, polyamideimide-based resins, diallyl phthalate-based resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, cellulose-based resins, poly(meth)acrylic resins, polyvinylidene chloride-based resins, acetal-based resins, and fluorine-based resins.
[0083] Specific examples of paper include strong sizing bleached or unbleached paper base materials for paper layers, or paper base materials such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, and the like. Specific examples of the metal foil include aluminum foil, copper foil, and stainless steel foil. A specific example of the metal of the inorganic vapor deposition layer is aluminum. Specific examples of inorganic oxides in the inorganic vapor deposition layer include silica, alumina, indium tin oxide, zinc oxide, tin oxide, titanium oxide, zirconium oxide, vanadium oxide, barium oxide, chromium oxide, silicon nitride, silicon carbide, etc. Among these, silica and alumina are preferred.
[0084] <Sealant layer> The sealant layer may be composed of a single layer, or may be composed of two or more layers having the same or different compositions. The sealant layer is a layer for heat sealing when forming an oxygen-absorbing in-mold labeled container, and therefore preferably contains a resin having heat sealability.
[0085] The sealant layer may contain any additives within the range that does not significantly impair the effects of the present invention. Examples of the additives include various resin additives that are generally used to adjust the moldability, productivity, and various physical properties of the resin film, such as antiblocking agents, slip agents, antioxidants, pigments, flow control agents, flame retardants, fillers, ultraviolet absorbers, and surfactants. The thickness of the sealant layer is preferably from 10 μm to 200 μm, and more preferably from 30 μm to 100 μm.
[0086] (Heat-sealable resin) Examples of resins having heat sealability include polyolefin resins, acid-modified polyolefin resins obtained by acid-modifying polyolefin resins by graft polymerization or copolymerization with unsaturated carboxylic acids or their anhydrides such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, and other resins. These resins can be used alone or in combination.
[0087] (Polyolefin resin) Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers.
[0088] The polyolefin resin may contain a resin derived from a fossil fuel and / or a resin synthesized using raw materials derived from plants. By containing a polyolefin resin derived from plants synthesized using raw materials derived from plants, the environmental load can be reduced. The plant-derived polyolefin resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived polyolefin resin used in combination and the application of the sealant layer. The content of the plant-derived polyolefin resin in the sealant layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the biomass degree of the sealant layer A or B or the laminate will be low, and the effect of reducing the environmental load will be reduced. The biomass ratio of the oxygen absorbing laminate of the present invention is preferably 10% or more and 50% or less. If it is less than the above range, the reduction in environmental load is small, and if it is more than the above range, the hand-tearability and drop impact resistance of the laminate are likely to decrease. The biomass degree of the sealant layer A or B is preferably 10% or more and 20% or less. If it is less than the above range, the reduction in environmental load is small, and if it is more than the above range, the hand-tearability and drop impact resistance of the laminate are likely to decrease. When the sealant layer has a multi-layer structure, the sealant layer may have a layer containing a plant-derived polyolefin resin and a layer not containing a plant-derived polyolefin resin. For example, it is preferable that the layer on the outer surface of the sealant layer that is the outermost surface of the laminate does not contain a plant-derived polyolefin resin. Furthermore, when the sealant layer has a multi-layer structure of three or more layers, it is preferable that the layer on the outer surface that is the outermost surface of the laminate and the layer on the inner surface that contacts other layers do not contain a plant-derived polyolefin resin, and the inner layer contains a plant-derived polyolefin resin.
[0089] Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively. Common polymerization methods include, for example, a high-pressure method for low-density polyethylene, and a low-pressure polymerization method (gas phase polymerization using a Ziegler-Natta catalyst or liquid phase polymerization using a metallocene catalyst), slurry method, solution method, gas phase polymerization method, etc. for linear low-density polyethylene.
[0090] (Method of forming sealant layer) The method for forming the sealant layer is not particularly limited, and may be any conventionally known method for laminating a sealant layer. The law can be applied. A sealant film consisting of one or more layers for the sealant layer may be prepared in advance, and the sealant film may be laminated by adhering it to other layers constituting the laminate via an adhesive, etc. The sealant film may be prepared by melt-extruding one or more resin compositions and forming them into a film by an inflation method, or by melt-extruding onto a roll and constricting it by an extrusion method using a T-die molding or the like to form a film. Here, it is preferable to subject one side of the prepared sealant film to a corona treatment, and then to adhere and laminate the film with the corona-treated side facing the side to be laminated. Alternatively, the resin composition for forming the sealant layer may be melted, melt (co)extruded, and poured onto the layers to be laminated, and a sealant layer consisting of one or more layers may be laminated onto the other layers that make up the laminate by an extrusion method using a T-die molding method using a feed block method or a multi-manifold method. In either method, a multi-layer sealant film can be produced by co-melt extrusion using resin compositions of the same or different compositions.
[0091] ≪Base material layer≫ As the material for the substrate layer, for example, a general known resin film having excellent mechanical, physical, chemical and other properties as a basic material for constituting an in-mold label container, particularly having strength, toughness and heat resistance, can be used. Furthermore, various paper substrates can be used, and a resin film and a paper substrate can be used in combination. The substrate layer may be composed of one layer, or may be composed of two or more layers of the same or different composition laminated by any lamination means. The thickness of the base layer can be appropriately set by those skilled in the art, but for the purpose of imparting appropriate strength and stiffness to the laminate, it is preferably 5 μm to 100 μm, more preferably 10 μm to 50 μm, and even more preferably 20 to 40 μm. In order to make the printed layer visible, it is preferable that the base layer that is on the outer side of the printed layer when forming an in-mold labeled container is colorless and transparent, and it is preferable that the layer made of a paper base material is laminated on the inner side of the printed layer.
[0092] Specific examples of the resin film include resin films made of tough thermoplastic resins, such as polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate, polyolefin-based resins such as polypropylene, polyamide-based resins such as nylon, polyaramid-based resins, polycarbonate-based resins, polyacetal-based resins, fluorine-based resins, and others. The resin film may be either an unstretched film or a uniaxially or biaxially stretched film. Among the above, a biaxially oriented PET film and a biaxially oriented polypropylene film are preferably used. Furthermore, in order to improve moisture resistance and adhesion to the injected resin, a multilayer resin film can be used in which polyvinylidene chloride (PVDC) is coated on the above resin film, or a multilayer resin film laminated with polyethylene, polypropylene, cyclic olefin copolymer, fluororesin, etc.
[0093] The resin used in the resin film may contain a resin derived from fossil fuels and / or a resin synthesized using raw materials derived from plants. By containing a plant-derived resin synthesized using raw materials derived from plants, the environmental load can be reduced. The plant-derived resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived resin used in combination and the application of the base layer. The content of plant-derived resin in the resin film is 40% by mass or more and 100% by mass or less. If the ratio is smaller than the above range, the biomass degree of the base layer and the laminate will be low, and the effect of reducing the environmental load will be reduced. When the layer made of the resin film of the base layer is a multi-layer structure, the layer made of the resin film of the base layer may have a layer containing a plant-derived resin and a layer not containing a plant-derived resin. For example, it is preferable that the layer on the outer surface that is the outermost surface of the laminate does not contain a plant-derived resin. Furthermore, when the layer made of the resin film of the base layer is a multi-layer structure of three or more layers, it is preferable that the layer on the outer surface that is the outermost surface of the laminate and the layer on the inner surface that is in contact with other layers do not contain a plant-derived resin, and the inner layer contains a plant-derived resin.
[0094] The paper base material can impart shapeability, flex resistance, rigidity, etc., and for example, a strong sizing bleached or unbleached paper base material for a paper layer, or a paper base material such as pure white roll paper, kraft paper, paperboard, coated paper, processed paper, milk base paper, etc. can be used. The paper base material has a basis weight of approximately 30 g / m 2 ~600g / m 2 The preferred basis weight is about 50 g / m 2 ~450g / m 2The order is more preferable.
[0095] If necessary, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments may be added to the resin film used for the base layer for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mildew resistance, electrical properties, strength, and the like. The amount of these additives may be arbitrarily added depending on the purpose as long as it does not adversely affect other performance properties. The substrate layer can be laminated with other layers via an adhesive layer. Furthermore, if necessary, in order to strengthen the adhesive strength between the substrate layer and the adhesive layer, the surface of the substrate layer that contacts the adhesive can be previously subjected to physical surface treatment such as corona discharge treatment, ozone treatment, plasma treatment, glow discharge treatment, sandblasting treatment, etc., or chemical surface treatment such as oxidation treatment using chemicals.
[0096] ≪Printing layer≫ The printed layer visually presents design patterns such as letters, numbers, figures, symbols, pictures, patterns, etc. for the purpose of decoration, indication of contents, indication of expiration date, indication of manufacturer, seller, etc., and for imparting aesthetic appeal, and can form the desired design pattern. The printing layer is preferably formed on one or both sides of the base layer by a printing method such as gravure printing, flexographic printing, or inkjet printing. The printing layer may be provided on the entire surface of the printed surface, or may be provided on only a part of the surface. For example, when the printing layer is provided on the surface of the laminate, the inkjet printing method is simple and preferable. By forming the printed layer inside the oxygen-absorbing laminate, the adhesion of the printed layer can be improved, and the ink on the printed layer can be prevented from being rubbed off or peeled off due to external impact or friction. The position of the printed layer in the laminate is not particularly limited, and it may be the outermost layer, or may be laminated inside the base layer and / or sealant layer. However, in order to make the printed layer visible, it is preferable that the layer that is on the outer side of the printed layer when the in-mold label container is formed is transparent.
[0097] <General-purpose adhesive layer> A general-purpose adhesive layer or anchor coat layer may be included between each of the layers constituting the oxygen-absorbing laminate. The general-purpose adhesive layer may be, for example, a layer (extruded resin layer) formed by a (co)extrusion lamination method in which an adhesive resin composition is melt-extruded, a T-die (co)extrusion method, or the like, or may be a layer (dry laminate layer) formed by dry lamination using a dry laminate adhesive. The resin contained in the adhesive resin composition is, for example, a polyolefin resin. Alternatively, polyolefin resins may be acid-modified by graft polymerization or copolymerization with an unsaturated carboxylic acid or its anhydride, such as acrylic acid, methacrylic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, etc., to give acid-modified polyolefin resins, polyvinyl acetate resins, poly(meth)acrylic resins, polyvinyl chloride resins, and other resins. These resins may be used alone or in combination.
[0098] Specific examples of polyolefin resins include polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-α-olefin copolymers polymerized using a metallocene catalyst, polypropylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol copolymers, ionomer resins, ethylene-acrylic acid copolymers, ethylene-ethyl acrylate copolymers, ethylene-methacrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-propylene copolymers, methylpentene (co)polymers, butene (co)polymers, polyisoprene, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers, and cyclic olefin (co)polymers such as polynorbornene. The copolymers may be random or block copolymers. Polyolefin resins are classified into, for example, polyethylene resins and polypropylene resins depending on the skeleton of the monomer used in the synthesis of the polyolefin, and may be copolymers. In the present invention, the term "polyethylene resin" is added as a general term for various types, and for example, polyethylene resin is also used as a general term for various types of polyethylene. Polyolefins produced by polymerizing α-olefins such as ethylene, propene, 1-butene, 1,3-butadiene, and 1-hexene as raw materials are called polyethylene-based resins, polypropylene-based resins, polybutylene-based resins, polybutadiene-based resins, polyhexene-based resins, and the like, respectively.
[0099] The general-purpose adhesive layer may contain additives such as antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, antiblocking agents, flame retardants, crosslinking agents, and colorants, as long as the additives do not impair the properties of the present invention. The thickness of the general-purpose adhesive layer is not particularly limited, but is preferably 1 g / m 2 Over 20g / m 2 The thickness of the extruded resin layer is preferably 1 μm or less, or 1 μm or more and 20 μm or less. By setting the numerical value within the above range, it is possible to obtain a stable adhesive strength. In addition, examples of dry lamination adhesives that can be used to form the general-purpose adhesive layer formed by dry lamination include two-component curing urethane adhesives, polyester urethane adhesives, polyether urethane adhesives, acrylic adhesives, polyester adhesives, polyamide adhesives, polyvinyl acetate adhesives, epoxy adhesives, rubber adhesives, and others.
[0100] The anchor coat layer is a layer formed by applying and drying an anchor coat agent, and can improve the adhesion between adjacent layers. The anchor coating agent may be any resin having a heat resistant temperature of 135° C. or higher, such as a vinyl modified resin, an epoxy resin, a urethane resin, a polyester resin, or a polyethyleneimine. Among the above, a curable anchor coating agent that contains a polyacrylic or polymethacrylic resin (polyol) having two or more hydroxyl groups in one molecule as a base agent and an isocyanate compound as a curing agent is particularly preferred. A silane coupling agent may also be used in combination, and nitrocellulose may also be used in combination to improve heat resistance. The thickness of the anchor coat layer is not particularly limited, but is preferably, for example, 0.05 μm or more and 1 μm or less.
[0101] <Functional layer> Examples of functional layers include layers made of resins that have barrier properties against oxygen gas, water vapor, etc., and / or have low adsorption of fragrance ingredients contained in the contents to be filled and packaged, and thus have excellent aroma retention, and further have properties that do not cause changes in taste or unpleasant odors, and that can be extruded, and layers made of light-shielding materials (light-shielding layers) can be mentioned.
[0102] Specific examples of the resin that can be used include polyacrylic resins, polymethacrylic resins, polyacrylonitrile resins, polymethacrylonitrile resins, polystyrene resins, polycarbonate resins, polyethylene terephthalate resins, or resins in which a portion of the ethylene component and / or terephthalate component thereof is copolymerized or modified with other di- or higher polyhydric alcohol components or dicarboxylic acid components, or polyester resins such as polyethylene naphthalate resins, polyamide resins, saponified ethylene-vinyl acetate copolymers, polyvinyl alcohol resins, polyvinyl chloride resins, polyvinylidene chloride resins, and other resins.
[0103] Among the above-mentioned resins, it is preferable to use a resin that has aroma retention and also has barrier properties against oxygen gas or water vapor, etc., and specifically, it is preferable to use a resin that is rich in aroma retention and barrier properties, such as a saponified ethylene-vinyl acetate copolymer, a polyamide resin, a polyacrylonitrile resin, or a polyester resin.
[0104] The resin may contain a resin derived from a fossil fuel and / or a resin synthesized using raw materials derived from plants. By containing a plant-derived resin synthesized using raw materials derived from plants, the environmental load can be reduced. Plant-derived resins with appropriate density and MFR can be selected depending on the physical properties of the fossil fuel-derived resin used in combination and the application of the functional layer. The content of the plant-derived resin in the functional layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the biomass degree of the functional layer and the laminate will be low, and the effect of reducing the environmental load will be reduced. When the functional layer has a multi-layer structure, the functional layer may have a layer containing a plant-derived resin and a layer not containing a plant-derived resin. For example, it is preferable that the layer on the outer surface, which is the outermost surface of the laminate, does not contain a plant-derived resin. Furthermore, when the reinforcing layer has a multi-layer structure of three or more layers, it is preferable that the layers on both surfaces of the functional layer do not contain a plant-derived resin, and the inner layer contains a plant-derived resin.
[0105] The light-shielding layer is a layer provided to prevent ultraviolet light and / or visible light from reaching the contents. The light-shielding layer can be formed using white ink mainly composed of titanium oxide or the like, black ink mainly composed of carbon black or the like, gray ink mainly composed of aluminum paste, colorant-colored resin film made light-shielding by adding pigments or dyes or the like, metal foil, metal vapor deposition film, or the like. As described above, when a metal foil such as an aluminum foil is used as the barrier layer, the barrier layer can also function as a light-shielding layer. These light-shielding materials can be used alone or in combination of two or more. When white ink, black ink or gray ink is used, the thickness of the light-shielding layer is preferably 4 μm or more and 12 μm or less, and more preferably 5 μm or more and 9 μm or less. In the case of aluminum foil, the thickness is preferably 5 μm to 30 μm, in the case of a metal vapor deposition film, the thickness is preferably 50 Å to 3000 Å, more preferably 100 Å to 1000 Å, and in the case of a colorant-colored resin film, the thickness is preferably 5 μm to 300 μm, more preferably 10 μm to 100 μm.
[0106] <Reinforcement layer> The reinforcing layer is a layer that imparts mechanical strength, deformation resistance, drop impact resistance, pinhole resistance, heat resistance, airtightness, quality maintenance, workability, sanitation, and the like to the laminate. The reinforcing layer may be formed from any of an extrusion or inflation-formed resin film, a resin coating film, synthetic paper, and the like.
[0107] Specific examples of the resin contained in the reinforcing layer include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-ethyl acrylate copolymer, ethylene-acrylic acid or methacrylic acid copolymer, methylpentene polymer, polybutene resin, polyvinyl chloride resin, polyvinyl acetate resin, polyvinylidene chloride resin, vinyl chloride-vinylidene chloride copolymer, poly(meth)acrylic resin, polyacrylonitrile resin, polystyrene resin, acrylonitrile-styrene copolymer (AS resin), acrylonitrile-butadiene-styrene copolymer (ABS resin), polyester resin, polyamide resin, polycarbonate resin, polyvinyl alcohol resin, saponified ethylene-vinyl acetate copolymer, fluorine resin, diene resin, polyacetal resin, polyurethane resin, cellulose, nitrocellulose, and other known resins.
[0108] The resin may contain a resin derived from a fossil fuel and / or a resin synthesized using raw materials derived from plants. By containing a plant-derived resin synthesized using raw materials derived from plants, the environmental load can be reduced. The plant-derived resin can be selected with an appropriate density and MFR depending on the physical properties of the fossil fuel-derived resin used in combination and the application of the reinforcing layer. The content of the plant-derived resin in the reinforcing layer is preferably 40% by mass or more and 100% by mass or less. If it is less than the above range, the biomass content of the reinforcing layer and the laminate will be low, and the effect of reducing the environmental load will be reduced. When the reinforcing layer has a multi-layer structure, the reinforcing layer may have a layer containing a plant-derived resin and a layer not containing a plant-derived resin. For example, it is preferable that the outer surface layer that is the outermost surface of the laminate does not contain a plant-derived resin. Furthermore, when the reinforcing layer has a multi-layer structure of three or more layers, it is preferable that the layers on both surfaces of the reinforcing layer do not contain a plant-derived resin and the inner layer contains a plant-derived resin.
[0109] The resin film may be either unstretched or uniaxially or biaxially stretched. The thickness of the reinforcing layer is not particularly limited, but can be selected from the range of about several μm to 300 μm.
[0110] <Method of producing oxygen absorbing laminate for in-mold label> A method for producing an oxygen absorbing laminate for in-mold label using the above-mentioned materials will be described below. The production method shown below is one example and does not limit the present invention. The layers constituting the oxygen-absorbing laminate for in-mold labels can be laminated by any method used in the production of ordinary packaging materials, such as wet lamination, dry lamination, solventless dry lamination, extrusion lamination, T-die coextrusion molding, coextrusion lamination, inflation molding, and the like. The oxygen-absorbing laminate for in-mold label of the present invention can also be subjected to secondary processing for the purpose of imparting surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, and biocompatibility. Examples of secondary processing include embossing, painting, adhesives, printing, metallizing (plating, etc.), machining, surface treatment (antistatic treatment, corona discharge treatment, plasma treatment, photochromic treatment, physical vapor deposition, chemical vapor deposition, coating, etc.), and the like. The laminate of the present invention can also be subjected to lamination (dry lamination or extrusion lamination), bag making, and other post-treatments.
[0111] When carrying out the above lamination, if necessary, the surface of each layer may be subjected to a pretreatment such as a corona treatment or an ozone treatment. In addition, for example, anchor coating agents such as isocyanate-based (urethane-based), polyethyleneimine-based, polybutadiene-based, and organic titanium-based anchor coating agents, or lamination adhesives such as polyurethane-based, polyacrylic-based, polyester-based, epoxy-based, polyvinyl acetate-based, cellulose-based, and others, can be optionally used.
[0112] As long as the base layer, the print layer, the oxygen barrier layer, the oxygen absorbing adhesive layer, and the sealant layer are laminated in this order, the order in which each layer is formed and laminated may be arbitrary. For example, an example will be described in which an oxygen-absorbing laminate for an in-mold label having a layer structure of a substrate layer / a printing layer / an oxygen barrier layer / an oxygen-absorbing adhesive layer / a sealant layer is produced. For example, a printing layer is first formed on the corona-treated surface of the substrate layer, and then an oxygen barrier layer is formed on the printing layer. Next, an oxygen-absorbing adhesive composition is applied to the laminated oxygen barrier layer, and dried as necessary to form an oxygen-absorbing adhesive layer. Then, a sealant film for the sealant layer is adhered onto the oxygen-absorbing adhesive layer to form a sealant layer. Then, an aging treatment is performed as necessary. In this manner, an oxygen-absorbing laminate for an in-mold label can be obtained.
[0113] <<Oxygen absorbing packaging material for in-mold labels>> The oxygen-absorbing packaging material for in-mold labels is a packaging material for in-mold labels, which is made from an oxygen-absorbing laminate for in-mold labels. The oxygen-absorbing packaging material for in-mold label may further include layers having various functions, if necessary.
[0114] <Oxygen absorbing in-mold label> The oxygen-absorbing in-mold label of the present invention is an in-mold label for an in-mold label container, which is made from the oxygen-absorbing packaging material for in-mold label of the present invention. In addition, added value can be added by various shape designs and printing decorations. The oxygen-absorbing in-mold label of the present invention is molded and laminated so as to be almost integral with other components in the oxygen-absorbing in-mold labeled container, and can give the appearance that the label design is printed directly on the oxygen-absorbing in-mold labeled container. For this reason, it is preferable that the oxygen-absorbing in-mold label has various shapes in accordance with the shape of the oxygen-absorbing in-mold label container to be formed. For example, the oxygen-absorbing in-mold label can be disposed at one or more locations on the in-mold labeled container, and adjacent oxygen-absorbing in-mold labels may be connected by a connecting portion. In particular, when oxygen-absorbing in-mold labels are arranged on the bottom and side surfaces of an in-mold-labeled container, a notch can be formed between the oxygen-absorbing in-mold label on the side surface and the oxygen-absorbing in-mold label on the bottom surface, as shown in Fig. 3. This notch may be provided in the oxygen-absorbing in-mold label on the side surface, or in the oxygen-absorbing in-mold label on the bottom surface.
[0115] <How to make oxygen absorbing in-mold labels> The oxygen-absorbing in-mold label is produced by molding and processing the oxygen-absorbing packaging material for in-mold labels into a shape and size that corresponds to the container to be laminated.
[0116] <Oxygen-absorbing in-mold label container> The oxygen-absorbing in-mold labeled container of the present invention is an in-mold labeled container produced using the oxygen-absorbing in-mold label of the present invention. In addition, added value can be added by various shape designs and printing decorations. For example, as shown in FIG. 2, an oxygen-absorbing in-mold labeled container consists of a lid part and a bottom part, and the bottom part has a structure in which a container-shaped molded body, injected resin, and an in-mold label are laminated and molded in a layered configuration with the injected resin interposed therebetween. In an oxygen-absorbing in-mold labeled container, the sealant layer of the oxygen-absorbing in-mold label is heat-sealed to the body and bottom of the injected resin, and the oxygen barrier layer is located outside the sealant layer of the oxygen-absorbing in-mold labeled container. The lid part is not particularly limited, but preferably has a heat seal layer for heat sealing to the bottom part. The shape of the lid part is, for example, a film-like shape, and has a shape that matches the outer periphery of the flange part of the bottom part, a shape that is slightly larger than the outer periphery, or a shape that partially protrudes from the outer periphery. The layer structure of the lid part is not particularly limited, but preferably has a heat seal layer for heat sealing to the bottom part, and can be formed from a packaging material including a layer structure such as PET / polyamide / easy peel PP sealant layer. The oxygen-absorbing in-mold label container can contain contents in the recess before the lid and bottom parts are heat-sealed together, and after the contents are contained, the flange of the bottom part and the film-like lid part are bonded together by heat sealing or adhesive, thereby protecting the contents by hermetic sealing. The contained contents can be removed by peeling off the lid part.
[0117] <Method of manufacturing oxygen-absorbing in-mold label container> The oxygen-absorbing in-mold labeled container can be produced, for example, by the following production method. The example given below is merely one example of the production method of the oxygen-absorbing in-mold labeled container of the present invention, and the present invention is not limited thereto. The bottom part of the oxygen-absorbing in-mold labeled container can be produced by a known method such as blow molding or injection molding. Blow molding involves setting an in-mold label on the inner wall of a mold split in two, pouring in a cylindrical resin, joining the molds together, and inflating the cylindrical resin with heat and air pressure, thereby molding the resin to the shape of the inner wall of the mold while laminating the in-mold label on the outside. This is particularly suitable for molding into bottle shapes for shampoos, detergents, etc. In the injection molding, an in-mold label is set on the inner wall of a concave mold, then a resin is injected and a convex mold is pressed against it to laminate the in-mold label, thereby forming an oxygen-absorbing in-mold-labeled container. At this time, a molded body that constitutes the inner wall of the oxygen-absorbing in-mold-labeled container can also be pressed against the convex mold. This is particularly suitable for containers for chilled beverages, dairy products, ice cream, etc. Here, in the above, when placing the packaging material for the lid parts on the bottom parts, one sheet of the packaging material for the lid parts may be placed on one bottom part and heat sealed, or one sheet of the packaging material for the lid parts may be placed on two or more bottom parts and heat sealed. Moreover, the two or more bottom parts may be cut separately or connected.
[0118] The lid formed by heat-sealing the packaging material for the lid part is then shaped into a shape that matches the outer periphery of the flange part of the bottom part, a shape that is one size larger than the outer periphery in an annular shape, or a shape that partially protrudes. Cut into pieces. As another manufacturing method, the packaging material for the lid part may be cut in advance into a shape that matches the outer periphery of the flange portion of the bottom part, a shape that is one size larger in an annular shape than the outer periphery, or a shape that partially protrudes, and then the material may be placed on the bottom part and heat sealed. Furthermore, when producing an oxygen-absorbing in-mold labeled container filling that contains and packages contents, it is preferable to place the contents in the recess of the bottom part before the above-mentioned heat sealing, and then perform the above-mentioned sheet sealing. In the above, the heat sealing can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, flame sealing, etc.
[0119] The present invention will be described in more detail below with reference to examples and comparative examples. EXAMPLES
[0120] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples.
[0121] <Raw materials> The main raw materials used in the examples are as follows: [Raw materials for oxygen absorbing compounds] Polypropylene ether diol 1: SANNIX PP-1000, manufactured by Sanyo Chemical Industries, Ltd. Number average molecular weight: 1000. Polypropylene ether diol 2: SANNIX PK-400, manufactured by Sanyo Chemical Industries, Ltd. Number average molecular weight: 400. Hydroxyl-terminated polyisoprene 1: Poly ip, manufactured by Idemitsu Kosan Co., Ltd. Number average molecular weight: 2500. ·Hydroxyl-terminated polybutadiene 1: Poly bd R15HT manufactured by Idemitsu Kosan Co., Ltd. Number average molecular weight 1200. Hydroxyl-terminated 1,2 addition polymer of 1,3-butadiene. Toluene diisocyanate 1: Coronate T-65, manufactured by Tosoh Corporation. · Oxygen absorbing compound 1: 3a,4,5,6,7,7a-hexahydro-4,7-methano-1H-inden-6-ol. · Oxidation promotion catalyst solution 1: Octope AE, manufactured by Hope Pharmaceutical Co., Ltd. A 4% ethyl acetate solution of cobalt octoate, an oxidation promotion catalyst. · Oxidation-promoting catalyst solution 2: Aceto-pe Mn(III) manufactured by Hope Pharmaceutical Co., Ltd. A 10% ethyl acetate solution of acetylacetone manganese(III), an oxidation-promoting catalyst.
[0122] [General-purpose adhesive] DL Adhesive 1: Two-component curing polyester urethane adhesive manufactured by Rock Paint Co., Ltd. [Film for base layer and barrier layer] OPP film 1: FOR-BT-A manufactured by Futamura Chemical Co., Ltd. Biaxially oriented PP film. 30μm thick. · Transparent vapor-deposited PET film 1: IB-PET manufactured by Dai Nippon Printing Co., Ltd. One-sided transparent alumina vapor-deposited PET film. 12μm thick. Aluminum-deposited PET film 1: 1310 manufactured by Toray Film Processing Co., Ltd. Aluminum-deposited PET film. 12μm thick.
[0123] [Printing layer ink] Gravure ink 1: Finart manufactured by DIC Graphics Corporation. [Sealant layer film] Heat seal OPP film 2: FOR-MH manufactured by Futamura Chemical Co., Ltd. Biaxially stretched heat Sealing PP film. 30μm thick. [In-mold label container material] Base sheet A: PBP-W200 manufactured by Idemitsu Unitech Co., Ltd. A co-extruded film with a layer structure of PE / EVOH / PE. Lid sheet A: transparent vapor-deposited PET film 1 (12 μm) / DL adhesive 1 (3 g / m 2 ) / Nylon film 1 (15 μm) / CPP film 1 (50 μm). Nylon film 1 is the emblem ONBC manufactured by Unitika Co., Ltd. CPP film 1 is EP-7R manufactured by Dai Nippon Printing Co., Ltd. Injection molding resin 1: Polypropylene, BC05B, manufactured by Japan Polypropylene Co., Ltd.
[0124] <Preparation of raw material solutions> (Synthesis of polyol 1 and preparation of polyol solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, a rectification column, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200°C with stirring. Ethylene glycol 53.8 parts by mass Neopentyl glycol 180.3 parts by mass 1,6-Hexanediol 204.6 parts by mass Isophthalic acid 287.8 parts by mass Adipic acid 273.5 parts by mass When the acid value of the solid content of the reaction liquid reached 15 mgKOH / g, the dehydration reaction was further allowed to proceed at 200 to 240° C. while blowing in nitrogen. When the acid value of the solid content of the reaction liquid became 10 mgKOH / g or less, the internal pressure was reduced to 30 Torr and the reaction was continued. When the acid value of the solid content of the reaction liquid became 3 mgKOH / g or less, the reaction was terminated and the liquid was cooled to room temperature to obtain Polyol 1. The number average molecular weight of the resulting polyester polyol, Polyol 1, was 2,000. Next, polyol 1 was dissolved in ethyl acetate to prepare a polyol solution 1 having a solid content of 60% by mass.
[0125] (Synthesis of polyol 2 and preparation of polyol solution 2) The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was heated with stirring to carry out a reflux reaction for 6 hours. Polypropylene ether diol 1 300.0 parts by mass Polypropylene ether diol 2 250.0 parts by mass Toluene diisocyanate 1 104.0 parts by mass Ethyl acetate 163.5 parts by mass When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the reaction mixture was cooled to obtain polyol 2. The number average molecular weight of the resulting urethane chain extended polyol, polyol 2, was 2,000. Next, polyol 2 was dissolved in ethyl acetate to prepare a polyol solution with a solid content of 60% by mass.
[0126] (Preparation of polyisocyanate solution 1) The following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser and stirred to obtain a polyisocyanate solution 1 having a solid content of 60% by mass. Hexamethylene diisocyanate (buret form) 100.0 parts by mass Ethyl acetate 66.7 parts by mass
[0127] [Table 1]
[0128] <Synthesis of oxygen absorbing compound and preparation of oxygen absorbing compound solution> [Oxygen absorbing compound 2] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Isophorone diisocyanate 74.0 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 2. Then, the oxygen-absorbing compound 2 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 2 having a solid content of 80 mass %.
[0129] [Oxygen absorbing compound 3] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyisocyanate solution 1 212.5 parts by weight When it was confirmed that the content of NCO groups in the solid content of the reaction liquid by the amine equivalent method reached approximately 0.64 mass %, the synthesis was terminated, the liquid was cooled, and the solvent was removed to obtain oxygen-absorbing compound 3. Then, the oxygen-absorbing compound 3 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 3 having a solid content of 60 mass %.
[0130] [Oxygen-absorbing compound 4] First, the following raw materials were added to a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the mixture was reacted at an internal temperature of 80 to 90° C. for 8 hours with stirring. Oxygen absorbing compound 1 100.0 parts by mass Polyol solution 1 682.3 parts by mass Polyisocyanate solution 1 265.6 parts by mass When it was confirmed that the absorption of the isocyanate group had completely disappeared in the infrared absorption spectrum, the synthesis was terminated, and the mixture was cooled and the solvent was removed to obtain oxygen-absorbing compound 4. Then, the oxygen-absorbing compound 4 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 4 having a solid content of 60 mass %.
[0131] [Oxygen-absorbing compound 5] Oxygen absorbing compound 5 was obtained in the same manner as in the above-mentioned oxygen absorbing compound 4, except that polyol solution 2 was used instead of polyol solution 1. Then, the oxygen-absorbing compound 5 was dissolved in ethyl acetate to prepare an oxygen-absorbing compound solution 5 having a solid content of 60 mass %.
[0132] [Oxygen-absorbing compound 6] The following raw materials were charged into a flask equipped with a nitrogen inlet tube, a stirrer, and a condenser, and the reaction was carried out for 6 hours at an internal temperature of 80 to 90°C with stirring. Hydroxyl-terminated polyisoprene 1 100.0 parts by mass Isophorone diisocyanate 4.7 parts by weight When it was confirmed by infrared absorption spectroscopy that the absorption of the isocyanate group had completely disappeared, the synthesis was terminated and the mixture was cooled to obtain oxygen-absorbing compound 6, which was a urethane polyol. The number average molecular weight of the obtained oxygen absorbing compound 6 was 7,000. Then, the oxygen absorbing compound 6 was dissolved in ethyl acetate to prepare an oxygen absorbing compound solution 6 having a solid content of 60 mass %.
[0133] Table 2 shows the composition of the reaction solution used in synthesizing oxygen-absorbing compounds 2 to 6. Moreover, the charged compositions of oxygen-absorbing compound solutions 2 to 6 are summarized in Table 3.
[0134] [Table 2]
[0135] [Table 3]
[0136] <Preparation of oxygen-absorbing adhesive composition> (Preparation of oxygen-absorbing adhesive composition A1) The following raw materials were mixed at room temperature and homogenized to obtain an oxygen-absorbing adhesive composition A1, which was then subjected to various evaluations. Oxygen absorbing compound solution 2 100 parts by mass Polyol solution 1 100 parts by weight Polyisocyanate solution 1 10 parts by weight Oxidation promoting catalyst solution 1 1 part by mass Ethyl acetate 140 parts by weight
[0137] (Preparation of oxygen-absorbing adhesive compositions A2 to A9, B1, and B2) According to the formulations in Tables 4 and 5, oxygen-absorbing adhesive compositions A2 to A9, B1, and B2 were obtained in the same manner as for oxygen-absorbing adhesive composition A1.
[0138] [Table 4]
[0139] [Table 5]
[0140] [Table 6]
[0141] [Example 1] (Preparation and evaluation of oxygen absorbing laminate for in-mold label) A print layer was formed on the corona-treated surface of OPP film 1 by gravure printing using gravure ink 1. Then, DL adhesive 1 was applied to the printed surface in a dry amount of 3 g / m 2 Apply and dry so that Thereafter, the deposited surface of the transparent deposited PET film 1 was placed opposite to the other and laminated by dry lamination to obtain a laminated film. Next, the oxygen absorbing adhesive composition A1 was applied to one surface of the transparent vapor-deposited PET film of the obtained laminated film in a dry amount of 3 g / m 2 After applying and drying, heat The adhesive OPP film 2 was dry laminated and aged at 40°C for 3 days to obtain an oxygen absorbing laminate for in-mold labeling. Various evaluations were carried out. Layer structure: OPP film 1 (30 μm) / printing layer / DL adhesive 1 (3 g / m 2 ) / transparent steam Adhesive composition A1 / Heat-sealed OPP film 2 (30 μm)
[0142] (Production and evaluation of oxygen-absorbing in-mold label containers) In order to manufacture the oxygen-absorbing in-mold labeled container 50 shown in FIG. 2, first, a container part molded body 30 was prepared in advance from a base material sheet A by vacuum molding. Next, the oxygen-absorbing in-mold label 10 shown in Fig. 3 was produced from the oxygen-absorbing laminate for in-mold label produced above. This oxygen-absorbing in-mold label 10 was combined with the container part molded body 30 prepared above to form a bottom part 51 of an oxygen-absorbing in-mold label container 50 as shown in Fig. 4. First, as shown in FIG. 5, the container part molded body 30 is attached to the upper die. Then, as shown in FIG. 6, the oxygen-absorbing in-mold label 10 is attached to the cavity of the lower mold. The particles were adsorbed onto the inner wall of the tube. Then, as shown in FIG. 7, the upper and lower dies were brought together and clamped. Next, while maintaining the mold clamped state, injection molding resin A was injected from the gate portion (pouring outlet) of the lower mold through the gate hole 12a of the oxygen-absorbing in-mold label 10 into the space between the upper mold and container part molded body 30 and the lower mold and oxygen-absorbing in-mold label 10, joining the container part molded body 30 and the oxygen-absorbing in-mold label 10 to obtain the bottom part 51 of the oxygen-absorbing in-mold label container 50. Then, the sealant layer of the cover material sheet A40 was laminated against the flange portion of the bottom part 51 of the obtained oxygen-absorbing in-mold labeled container 50, and heat-sealed to obtain the oxygen-absorbing in-mold labeled container 50 shown in Figure 2.
[0143] [Examples 2 to 9, Comparative Examples 1 and 2] Except for changing the oxygen-absorbing adhesive composition A1 of Example 1 to any of oxygen-absorbing adhesive compositions A2 to A9, B1, B2, or DL Adhesive 1 according to the description in Table 7, the same procedures as in Example 1 were performed to obtain an oxygen-absorbing laminate for in-mold labels, an oxygen-absorbing in-mold label 10, a bottom part 50 of an oxygen-absorbing in-mold labeled container, and an oxygen-absorbing in-mold labeled container 50, and these were evaluated in the same manner.
[0144] [Example 10] Except for changing the oxygen barrier layer of Example 1 from transparent vapor-deposited PET film 1 to aluminum vapor-deposited PET film 1 in accordance with the description in Table 7, the same procedures as in Example 1 were carried out to obtain an oxygen-absorbing laminate for in-mold label, an oxygen-absorbing in-mold label 10, a bottom part 50 of an oxygen-absorbing in-mold labeled container, and an oxygen-absorbing in-mold labeled container 50, and these were evaluated in the same manner. [Comparative Example 3] Except for changing the oxygen-absorbing adhesive 1 to DL adhesive 1, the same procedure as in Example 10 was repeated to obtain a laminate, which was then evaluated in the same manner.
[0145] [Table 7]
[0146] <Summary of Results> Oxygen absorbing laminate for in-mold label, in-mold label, oxygen absorbing The in-mold labeled containers exhibited a balance of excellent laminate strength, oxygen uptake, and low odor. On the other hand, the laminate, in-mold label, and in-mold labeled container of the comparative examples showed poor results in any of the lamination strength, oxygen absorption amount, and low odor properties.
[0147] <Evaluation method>
[0148] [Oxygen absorption] After replacing the contents storage area of the in-mold label container with nitrogen, heat seal the lid part while replacing it with nitrogen, and apply 1400cc / m2 of liquid to the inner surface area of the container with a syringe. 2 Air, oxygen The oxygen concentration in the pouch was measured using a non-destructive oxygen concentration meter after storing it in a thermostatic chamber at 25°C for 14 days, and the amount of oxygen absorbed was calculated. The oxygen concentration was measured using a non-destructive oxygen concentration meter (FIBOX4 OXYGEN METER) manufactured by Presence.
[0149] [Laminate strength] A rectangular test piece 15 mm wide was prepared from the obtained oxygen-absorbing laminate, and the laminate strength between the layers via the oxygen-absorbing adhesive layer was measured using a tensile tester at a tensile speed of 50 mm / min.
[0150] [Odor sensory evaluation] After measuring the amount of oxygen absorbed, the inside of the blister packaging container was smelled and the odor was judged according to the following criteria. Note that the odor originating from the sealant layer was excluded from the judgment. Evaluation criteria: 0: Odorless 1: Faint odor 2: Weak odor 3: Moderate odor 4: Strong odor
[0151] [Retort resistance] The inside of an in-mold label container with a heat-sealed lid was filled with water and subjected to aerated retort treatment at 121°C for 30 minutes, after which the presence or absence of delamination was visually detected. The meanings of the descriptions in the table are as follows: ○: No delamination ×: Delamination present
[0152] [Microwave resistant] The inside of an in-mold label container with a heat-sealed lid was filled with water and heated in a microwave oven at 600W for 2 minutes, and the presence or absence of delamination was visually detected. The meanings of the descriptions in the table are as follows. ○: No delamination ×: Delamination present [Explanation of symbols]
[0153] 1. Oxygen-absorbing laminate for in-mold labels 2 Base material layer 3 printing layer 4. Oxygen Barrier Layer 5 Oxygen-absorbing adhesive layer 6 Sealant Layer 10 In-mold label 11, 11a, 11b, 11c, 11d Body in-mold label 12 Bottom In-mold Label 12a Gate hole 13 Connecting part 14 Notch 30 Container part molding 31 Container part molded body curved part 30 Container part molding 30a Container part molded body 30b Container part molded body bottom 30c Container part molded body flange portion 33 Container part molded body gate receiving part 40 Lid parts 50 In-mold label container 51 Bottom parts 52a Injection resin flange part 52b Injected resin body 52c injection resin bottom 60 Lower mold 61 Upper mold
Claims
1. An oxygen-absorbing laminate for in-mold labeling, comprising at least a base layer, an oxygen barrier layer, an oxygen-absorbing adhesive layer, and a sealant layer laminated in this order, and further comprising a printed layer, said oxygen-absorbing laminate being used for an in-mold label container, The oxygen-absorbing adhesive layer is a layer formed from an oxygen-absorbing adhesive composition, The oxygen-absorbing adhesive composition contains at least an oxygen-absorbing compound and an oxidation-promoting catalyst, The oxygen absorbing compound has one or more unsaturated five-membered rings at the terminal of the main chain of the molecule, or at the terminals of the main chain and side chain of the molecule, any bond between the five carbon atoms constituting the unsaturated five-membered ring is a carbon-carbon double bond; A monovalent and / or divalent or higher electron-donating organic group 1 is bonded to the unsaturated five-membered ring, When the number of the unsaturated five-membered ring is one, the five-membered ring or the organic group 1 has a functional group having an active hydrogen or a group in which the active hydrogen of the functional group having an active hydrogen is substituted with a monovalent organic group 2, When the number of the unsaturated five-membered rings is two or more, the unsaturated five-membered rings are bonded to each other via a divalent or higher organic group 2 which substitutes an active hydrogen of an active hydrogen group on each of the five-membered rings or the organic group 1. Oxygen absorbing laminate for in-mold labels.
2. the structure of the unsaturated five-membered ring or the structure consisting of the unsaturated five-membered ring and organic group 1 is derived from one or more members selected from the group consisting of cyclopentadiene, dicyclopentadiene, norbornene, and derivatives thereof; The oxygen-absorbing laminate for an in-mold label according to claim 1 .
3. The organic group 2 includes a structural portion derived from an isocyanate-based compound, or an isocyanate-based compound and a hydroxyl group-containing compound.
3. The oxygen-absorbing laminate for an in-mold label according to claim 1 or 2.
4. The isocyanate compound is xylene diisocyanate, hexamethylene diisocyanate, one or more selected from the group consisting of isocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof; The oxygen-absorbing laminate for an in-mold label according to claim 3 .
5. the hydroxyl group-containing compound is one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof; 5. The oxygen-absorbing laminate for an in-mold label according to claim 3 or 4.
6. The organic group 2 does not have a crosslinkable functional group.
6. The oxygen-absorbing laminate for an in-mold label according to claim 1.
7. The organic group 2 has one or more crosslinkable functional groups, the crosslinkable functional group is a hydroxyl group and / or an isocyanate group; 6. The oxygen-absorbing laminate for an in-mold label according to claim 1.
8. The oxygen-absorbing compound contains one or more compounds selected from the group consisting of compounds represented by the following formulas (1) to (4):
6. The oxygen-absorbing laminate for an in-mold label according to claim 1. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 (In the formula, a to e are each a number of 1 or more, and R 1 , R 2 , R 3 Each of the above is an organic group having one or more carbon atoms, contains at least an alkylene and / or phenylene structure, and further contains a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
9. The oxygen-absorbing compound contains a compound represented by the following formula (5):
6. The oxygen-absorbing laminate for an in-mold label according to claim 1. 【Chemistry 5】 (In the formula, f is a number of 0 or more, and R 4 and R 5 Each of the above is an organic group having one or more carbon atoms, containing at least an alkylene and / or phenylene structure, and may further contain a structure derived from one or more selected from the group consisting of polyhydric alcohols, polyolefin polyols, polyether polyols, polyester polyols, polycarbonate polyols, poly(meth)acrylic acid ester polyols, phenoxy resins, and urethane chain-extended polyols thereof.
10. The oxidation-promoting catalyst is a peroxide or a compound containing a cation of a transition metal.
10. The oxygen-absorbing laminate for an in-mold label according to claim 1.
11. The compound containing a cation made of a transition metal is a metal soap made of a transition metal compound capable of releasing a cation or complex made of a transition metal and an anion or ligand made of a fatty acid.
11. The oxygen-absorbing laminate for an in-mold label according to claim 1.
12. The oxygen absorbing adhesive composition further contains a modifier, The modifying agent contains an isocyanate compound and / or a hydroxyl group-containing compound.
12. The oxygen-absorbing laminate for an in-mold label according to claim 1.
13. The isocyanate compound is one or more selected from the group consisting of xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and derivatives thereof. The oxygen-absorbing laminate for an in-mold label according to claim 12.
14. The hydroxyl group-containing compound is selected from the group consisting of polyester polyols, poly(meth)acrylic acid ester polyols, polyalkylene ether diols, and urethane chain-extended polyols thereof. Contains one or more selected from the group consisting of: The oxygen-absorbing laminate for an in-mold label according to claim 12 or 13.
15. An oxygen-absorbing packaging material for in-mold labeling, produced using the oxygen-absorbing laminate for in-mold labeling according to any one of claims 1 to 14.
16. An oxygen-absorbing in-mold label produced using the oxygen-absorbing packaging material for in-mold label according to claim 15.
17. An oxygen-absorbing in-mold label container produced using the oxygen-absorbing in-mold label according to claim 16, The oxygen-absorbing in-mold label is in-molded onto the outer side surface of the body and / or the outer bottom surface of the bottom of the in-mold label container, The oxygen barrier layer is a layer located outside the oxygen absorbing adhesive layer. Oxygen absorbing in-mold label container.